Scorpion sting: Myriad presentation in PICU - Lokesh Tiwari; Manish Kumar; Manikant Srivastava (Wolters Kluwer Medknow Publications, 2019)
Scorpion sting is a major health problem in tropical and subtropical countries.[1] A total of 113 species are available in India[2]; of these Mesobuthus tumulus or Indian Red Scorpion is the most lethal.[1] Like many other neglected tropical diseases, due to gross under-reporting, reliable statistics of scorpion envenomation are not available. Even more concerning is the lack of awareness amongst pediatricians regarding the spectrum of manifestations of scorpion envenomation in children and its management in both primary and advanced care settings. We are reporting a series of 3 cases exemplifying the myriad manifestations of scorpion envenomation along with emphasizing the role of prazosin and supportive intensive care monitoring and management. This article also focusses on role of treatment options such as amiodarone and glucose-insulin infusion in management of scorpion envenomation induced myocardial dysfunction, refractory to first line inotropes.